Impact of population ageing on the cost of hospitalisations for cardiovascular disease: a population-based data linkage study - Ha, N.; Hendrie, Delia; Moorin, Rachael (BioMed Central, 2014)
Background: Cardiovascular disease (CVD) is the most costly disease in Australia. Measuring the impact of ageing on its costs is needed for planning future healthcare budget. The aim of this study was to measure the impact of changes in population age structure in Western Australia (WA) on the costs of hospitalisation for CVD. Methods: All hospitalisation records for CVD occurring in WA in 1993/94 and 2003/04 inclusive were extracted from the WA Hospital Morbidity Data System (HMDS) via the WA Data Linkage System. Inflation adjusted hospitalisation costs using 2012 as the base year was assigned to all episodes of care using Australian Refined Diagnosis Related Group (AR-DRG) costing information. The component decomposition method was used to measure the contribution of ageing and other factors to the increase of hospitalisation costs for CVD. Results: Between 1993/94 and 2003/04, population ageing contributed 23% and 30% respectively of the increase in CVD hospitalisation costs for men and women. The impact of ageing on hospitalisation costs was far greater for chronic conditions than acute coronary syndrome (ACS) and stroke. Conclusions: Given the impact of ageing on hospitalisation costs, and the disparity between chronic and acute conditions, disease-specific factors should be considered in planning for future healthcare expenditure.